Studi Meta-Analisis Hubungan Antara Social Support Dengan Ptsd (Post Traumatic Stress Disorder) - Siti Urbayatun (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2008)
Reason for this meta analysis study is the variance of relation between social support and Post Traumatic Syndrome Disorder (PTSD). Six (6) articles show that social support correlates negatively with PTSD. Especially affection, instrumental and activity support. Social support as buffer between stressors and PTSD. Key words : meta analysis, social support, post traumatic stress disorder (PTSD)